Investigation of the effect of zinc inclusion for tin perovskite based solar cells - Luna Puerta, Lidia (2015)
The third generation of solar cells, based on organic/inorganic perovskite absorbers promises to bring a breakthrough to the energy production with photovoltaic devices. Up-to-date, best results have been achieved with lead halide perovskite, reaching an efficiency of 20,1%. This project aims to provide a comprehensive study to introduce Zinc (Zn) element in the structure of an inorganic and efficient lead free perovskite. In the first part of the project the Zn was included independently so that it could occupy substitutional sites of Tin (Sn) and in the second part two mixtures of perovskite, one based on Sn, the second based on Zn, were mixed in different stoichiometric ratios to produce the hybrid Sn-Zn perovskite. The cells were produced by depositing the perovskite as well as the HTM by spincoating method. Different rations of Zn doping were tested, and best results achieved with the following composition of a two-phase perovskite of 80% CsSnI3 and 20% Cs2ZnI4, reaching a fill factor of 0.384 and a PCE of 1.3. Moreover, it was observed that the doping of Sn perovskite with Zn had some limits, since it was shown that for a CsSnxZn(1-x)I3 composition, there was a threshold of x=0.8 for which no more Zn could be introduced in the 3D perovskite, leading to the formation of a second 2D phase of Cs2ZnI4.